A Midsummer Night's Faery Tale - Froud, Wendy and Windling, Terri; Photographs by Jones, John Lawrence (New York Simon & Schuster, 1999)
Terri Windling and the brilliantly talented doll maker Wendy Froud present a charming and visually stunning faery tale about true love and simple truths.
Include Color Illustrations